2019
DOI: 10.1371/journal.pone.0218603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the welfare of extensively managed sheep

Abstract: The aim of this study was to identify the main on-farm welfare issues likely to be encountered in extensive sheep farming systems. Thirty-two commercial sheep farms in Victoria, Australia were involved in this study. Of the 32 farms involved, 30 were visited twice (at mid-pregnancy and weaning), and 2 farms only once (both at weaning). In total, 62 visits were conducted and 6,200 ewes (aged 2–5 years) were examined using six animal-based indicators: body condition score (BCS), fleece condition, skin lesions, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 34 publications
0
39
2
Order By: Relevance
“…The finding that 57 per cent of participants docked tails short closely aligned to that of a recent phone survey of Victorian farmers 24. However, there was an inconsistency identified between self-reported tail length data collected in this study and primary tail length data collected by Munoz et al 25. In this study, 43 per cent of participants self-reported to dock tails ETV, yet all participants had a percentage of short-tailed ewes (two to five years old) in the previous study; averages ranged from 41 to 100 per cent.…”
Section: Discussioncontrasting
confidence: 61%
“…The finding that 57 per cent of participants docked tails short closely aligned to that of a recent phone survey of Victorian farmers 24. However, there was an inconsistency identified between self-reported tail length data collected in this study and primary tail length data collected by Munoz et al 25. In this study, 43 per cent of participants self-reported to dock tails ETV, yet all participants had a percentage of short-tailed ewes (two to five years old) in the previous study; averages ranged from 41 to 100 per cent.…”
Section: Discussioncontrasting
confidence: 61%
“…Another concern for the semi-intensive and extensive farming systems is the compromised animal welfare because of heat stress. Developing practical technologies that assist in detecting welfare issues are necessary [ 4 ]. Body temperature is the most reliable indicator of heat stress; however, its determination under field conditions is arduous [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This present study is part of a larger research investigating farmer attitudes and sheep welfare outcomes. This paper reports on the relationship between farmer attitudes, management behaviour and sheep welfare and builds on a published study by Munoz et at., [22] that reports details on the on-farm welfare of extensively managed sheep.…”
Section: Introductionmentioning
confidence: 99%